FOR PROGNOSIS OF INNOVATIVE DEVELOPMENT OF ENTERPRISES (Globalization and Business, 2018)
The article highlights the main methodology about the elaborating prognosis resulting from actually of prognosis on the development of scientific –technical and innovative sphere. About their principles; if shows models of prognosis of innovative development, peculiarities of tasks that should be solved while choosing and fulfilling instruments, also specifies of original information and kinds of factors. The article has studied versions of macro economical development of prognosis, main stages of compiling prognosis and structural models. The work has examined and presented conclusions about main directions to support a state in innovative business, about completing the mechanism in innovative funding.